2020
DOI: 10.3390/antiox9050391
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Bound Methionine Sulfoxide (MetO) Levels and MsrB2 Abundance Are Differentially Regulated during the Desiccation Phase in Contrasted Acer Seeds

Abstract: Norway maple and sycamore produce desiccation-tolerant (orthodox) and desiccation-sensitive (recalcitrant) seeds, respectively. Drying affects reduction and oxidation (redox) status in seeds. Oxidation of methionine to methionine sulfoxide (MetO) and reduction via methionine sulfoxide reductases (Msrs) have never been investigated in relation to seed desiccation tolerance. MetO levels and the abundance of Msrs were investigated in relation to levels of reactive oxygen species (ROS) such as hydrogen peroxide, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 88 publications
3
32
0
Order By: Relevance
“…The first plant gene encoding methionine sulfoxide reductase B (MsrB) was identified in Arabidopsis while researchers were searching for homologs to the human selenoprotein X proteins [ 37 ]. Since that study was published, numerous studies have shown that MsrB enzymes are important factors involved in the regulation of multiple processes during plant development [ 28 , 29 ] as well as in the response to biotic and abiotic stress [ 23 , 24 , 25 , 29 ]. Châtelain et al [ 29 ] determined that the Msr repair system plays a decisive role in establishing and preserving seed longevity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The first plant gene encoding methionine sulfoxide reductase B (MsrB) was identified in Arabidopsis while researchers were searching for homologs to the human selenoprotein X proteins [ 37 ]. Since that study was published, numerous studies have shown that MsrB enzymes are important factors involved in the regulation of multiple processes during plant development [ 28 , 29 ] as well as in the response to biotic and abiotic stress [ 23 , 24 , 25 , 29 ]. Châtelain et al [ 29 ] determined that the Msr repair system plays a decisive role in establishing and preserving seed longevity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the abundance of MsrB2 correlates well with the time of storage, suggesting that this Msr isoform is important in maintaining seed quality during long-term storage. Moreover, it has recently been reported that the MsrB2 protein is involved in seed desiccation tolerance [ 28 ]. Importantly, the loss of desiccation tolerance also results in the loss of seed viability [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations